Extracellular vesicle‐coated nanoparticles. Issue 2 (7th December 2020) - Fathi, Parinaz; Rao, Lang; Chen, Xiaoyuan
Abstract: Synthetic nanoparticles have been used for a variety of theranostic applications to aid in the betterment of human health. These nanoparticles can provide platforms for targeted imaging and therapy of diseased tissues. The development of surface coatings for nanoparticles has enabled their selective uptake in tissues of interest, and the use of membrane‐derived nanoparticle coatings provides a particularly promising approach for the regulation of nanoparticle‐tissue interactions. Membranous extracellular vesicles (EVs) secreted by cells have been known to contain antigens, proteins, and other cell components on their surface that facilitate their uptake in target cells, enabling the transport of information from one cell to another. EV‐based nanoparticle coatings allow for the expansion of nanoparticle targeting from typical approaches that target individual antigens, to an approach that can simultaneously target many antigens for more efficient uptake within target cells. EV‐derived coatings also possess immune evasive properties that can lead to increased circulation time. In this mini‐review, we describe the various approaches and applications for EV coating of nanoparticles, a majority of which focus on cancer applications. We also provide an overview of commonly used EV sources for nanoparticle coating applications. Abstract : This article provides a review of nanoparticles coated with extracellular vesicles (EVs) and exosomes. The article describes common EV sources, nanoparticle coating methods, and applications. A major focus of the review is on the applications of EV‐coated nanoparticles in cancer therapy.